Neuroprotective Effects of Kinin B2 Receptor in Organotypic Hippocampal Cultures of Middle-Aged Mice - Toricelli, Mariana; Evangelista, Sebastiana Ribeiro; Oliveira, Larissa Rolim; Viel, Tania Araujo; Buck, Hudson Sousa (Frontiers in Aging Neuroscience, 2019)
Aging is a multifactorial phenomenon that results in several changes at cellular and molecular levels and is considered the main risk factor for some neurodegenerative diseases. Several evidence show the participation of the kallikrein-kinin system (KKS) in neurodegeneration and this system has been associated with inflammation and immunogenic responses in the central and peripheral systems by the activation of the B1 and B2 receptors. Previous work by our group showed that bradykinin (BK) and the B2 receptor played a possible role in neuroprotection. Therefore, the objective of this study was to evaluate the participation of B2 receptors in cell viability, neuroinflammatory response and neuroplasticity in organotypic hippocampal cultures (OHCs) of 6- and 12-month-old mice. It was observed that activation of the B2 receptor by bradykinin decreased the inflammatory response and increased plasticity in 12-month-old slices. Conversely, there was an increase in the inflammatory response and a decrease in neural plasticity in the 6-month-old slices. In both ages, an increase in cell viability was observed. This data suggests that the function of the kinin B2 receptor in the hippocampus is modulated by age, providing neuroprotective action in old age.